Challenges of Managing Colleges of Education in Nigeria: The Way Forward - MUHAMMAD, Musa, Ibrahim; Iliya, Ladan Vincent (International Journal of Educational Management, 2025)
Colleges of Education are the main institutions purposely designed for teacher training in Nigerian educational system. The goals of these institutions are to produce highly motivated, conscientious and efficient classroom teachers for basic and post basic schools and further encourage the spirit of enquiry and creativity in teachers. Since the last two decades, the matters about these colleges suggest that the institutions have lost their early glory. Therefore, some critical issues and challenges require solutions as education changes globally. Essential, they are expected to provide full time courses in teaching, instruction and training and to conduct courses in education for qualified teachers. It is rather unfortunate that effective management of Colleges of Education in Nigeria is faced with a lot of challenges, which have prevented the institutions from delivering on their mandate. Many COEs are in deplorable state, facing so much difficulties and challenges, thereby affecting their management for quality outputs. With the way Nigeria Government is handling the issues of funding and academic standard in education, prospects for effective management of colleges of education in the country in the years ahead do not seem bright. It is against this backdrop that this paper presents an overview of COEs in Nigeria and identified inadequate funding, lack of political will, deteriorated infrastructure, inadequate quality and quantity of staff, unnecessary political interferences in the selection of administrators, high students’ enrolment, poor education data bank and brain-drain syndrome as some of the challenges to effective management of Colleges of Education in Nigeria. Some suggestions were also put forward on how to improve on these challenges for effective management of Colleges of Education in Nigeria.